DEPRESSION AMONG HIGH SCHOOL STUDENTS: UNDETECTED, UNDERDIAGNOSED - Ziske Maritska (Lembaga Pengabdian pada Masyarakat, 2019)
Background. Depression is a condition that can not be taken lightly, in any age. It is one of the most significant risk factor for suicide, especially in adolescents. More over, depression can also interfere one’s social and educational life. Hence, recognizing it and treating it becomes pivotal, let alone in teenagers like high school students who are also at risk for suffering from depression. This study wished to identify the incidence of depression among high school students in Palembang, Indonesia.Method. This is an observational descriptive study towards 47 high school students in Palembang, Indonesia. Students who were eligible for the study were asked for informed concent before they participated in the study. They were then asked to fill in the Self Rating Questionnaire (SRQ) in order to screen depression among them.Result. Almost half of the high school students are having depression (42.55%). Most of them are females (51.35%) and are from the tenth grade, meaning they are the new students (57.14%).Conclusion. Depression is quite prevalent among adolescents, hence it needs special attention on how to prevent depression in teenagers.